Comparisons of two protocols for early treatment of anterior open bite. (3rd May 2016) - Mucedero, Manuela; Vitale, Maddalena; Franchi, Lorenzo; Cozza, Paola; Perillo, Letizia
Summary: Aim: The purpose of this study was to compare the outcomes of the treatment with the quad-helix/crib (Q-H/C) appliance with those of a combination of transpalatal arch, high-pull headgear, and lip bumper (TPA/HG/LB) in growing patients with anterior open bite malocclusion. Methods: The TPA/HG/LB sample consisted of 22 subjects, 16 girls and 6 boys (mean age 7.5±1.4 years at the start of treatment, T1, and 8.7±1.5 years at the end of active treatment, T2). The Q-H/C sample consisted of 28 subjects, 17 girls and 11 boys (mean age 8.2±1.3 years at T1, and 8.7±1.6 years at T2). Both treated groups were compared with a control group of 20 untreated subjects matched for dentoskeletal disharmony and observation interval. The changes from T2 to T1 between the three groups were compared with the analysis of variance. Results: Both TPA/HG/LB and Q-H/C groups exhibited greater reduction of the palatal plane to mandibular plane angle (−1.7° and −1.9°, respectively) and a significantly greater increase in overbite (2.2 and 2.3mm, respectively) with respect to controls. Conclusions: Q-H/C and TPA/HG/LB protocols were equally effective in correcting the anterior open bite.